TRAF2 Is a Novel Ubiquitin E3 Ligase for the Na,K-ATPase β-Subunit That Drives Alveolar Epithelial Dysfunction in Hypercapnia - Gabrielli, Nieves M.; Mazzocchi, Luciana C.; Kryvenko, Vitalii; Tello, Khodr; Herold, Susanne; Morty, Rory E.; Grimminger, Friedrich; Dada, Laura A.; Seeger, Werner; Sznajder, Jacob I.; Vadász, István (Frontiers in Cell and Developmental Biology, 2021)
Several acute and chronic lung diseases are associated with alveolar hypoventilation leading to accumulation of CO2 (hypercapnia). The β-subunit of the Na,K-ATPase plays a pivotal role in maintaining epithelial integrity by functioning as a cell adhesion molecule and regulating cell surface stability of the catalytic α-subunit of the transporter, thereby, maintaining optimal alveolar fluid balance. Here, we identified the E3 ubiquitin ligase for the Na,K-ATPase β-subunit, which promoted polyubiquitination, subsequent endocytosis and proteasomal degradation of the protein upon exposure of alveolar epithelial cells to elevated CO2 levels, thus impairing alveolar integrity. Ubiquitination of the Na,K-ATPase β-subunit required lysine 5 and 7 and mutating these residues (but not other lysines) prevented trafficking of Na,K-ATPase from the plasma membrane and stabilized the protein upon hypercapnia. Furthermore, ubiquitination of the Na,K ATPase β-subunit was dependent on prior phosphorylation at serine 11 by protein kinase C (PKC)-ζ. Using a protein microarray, we identified the tumor necrosis factor receptor-associated factor 2 (TRAF2) as the E3 ligase driving ubiquitination of the Na,K ATPase β-subunit upon hypercapnia. Of note, prevention of Na,K ATPase β-subunit ubiquitination was necessary and sufficient to restore the formation of cell-cell junctions under hypercapnic conditions. These results suggest that a hypercapnic environment in the lung may lead to persistent epithelial dysfunction in affected patients. As such, the identification of the E3 ligase for the Na,K-ATPase may provide a novel therapeutic target, to be employed in patients with acute or chronic hypercapnic respiratory failure, aiming to restore alveolar epithelial integrity.